Cut the commute and fly around less too - Banister, D (2008)
People are travelling more and further than they ever used to. This has enormous benefits but how can we reduce greenhouse gas emissions and yet retain the quality of communication? While there are ways and means to cut road travel, reducing travel by air will be a real challenge.